Knowledge and Awareness about Emotional Regulation Teaching Method among Special Education Teachers in Malaysia - Md Jais, Noraziyanah Md Jais; Low, Hui Min (Jurnal Pendidikan Bitara UPSI, 2024)
The effectiveness of the emotional regulation teaching method among special education teachers is one of the contributing factors to increasing emotional regulation among students with special needs. Therefore, this article aims to identify and discuss the knowledge level, sources’ level and awareness level of emotional regulation teaching methods among special education teachers in Malaysia. A descriptive quantitative study involving 35 respondents selected through the purposeful sampling technique was conducted. The findings disclosed that Malaysian special education needs (SEN) teachers possess a moderate understanding of emotional regulation concepts in general, while their grasp of emotional regulation as outlined in the special education curriculum is notably strong. However, it suggests that their knowledge seems confined to the curriculum guidelines, indicating a limited awareness of emotional regulation beyond these parameters. These findings shed light on the state of knowledge and awareness regarding emotional regulation teaching methods among special education teachers in Malaysia.